Measuring Human Capital Development (HCD) Return on Investment (ROI), Risk, and Knowledge Gaps across selected Occupations in South Africa - Govender, Cookie M.; Adegbite, Waliu Mulero (Journal of Management and Research, 2023)
Business challenges are experienced while measuring the economic value of Human Capital Development (HCD) as compared to their overall business performance and profitability. The HCD measurement challenge may be attributed to the knowledge gap on HCD measurement among employees and managers. A quantitative survey (n = 210) measured and compared management and employee knowledge on HCD Return on Investment (ROI), HCD risks, and HCD risk solutions in South Africa. Respondents ranged across occupational categories from various organizations. The findings indicated an awareness of HCD ROI measurement, risk, and risk remedies. However, there were deviations in that knowledge across occupational categories. General managers and entrepreneurs have better knowledge of HCD ROI measurement, risk identification, and risk remedies as compared to other occupations. HR, financial, hospitality, and learning and development professionals showed the lowest mean scores. The current study contributed to measure HCD ROI, risk, and occupational HCD knowledge gaps. The practical implication and contribution of the study was that managers and employees were made aware of the significance of measuring HCD ROI, risk, and remedies across all occupations. Moreover, further research is recommended to expand the research instrument and measure HCD knowledge across occupations in other countries in Africa and across the globe.